Essentials of Tibetan Traditional Medicine - Glover, Denise (Ethnobiology Letters, 2013)
Review of Essentials of Tibetan Traditional Medicine, Thinley Gyatso and Chris Hakim. 2010. North Atlantic Books, Berkeley. Pp. 416. 24.95 (paperback). ISBN 978‐1556438677.